Changes in specific jumping performance after detraining period - Kannas, T. M.; Amiridis, I. G.; Arabatzi, F.; Katis, A.; Kellis, E. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The purpose of this study was to examine the effects of a detraining period after specific plyometric training on vertical jump performance and mechanical properties of aponeurosis of medial gastrocnemius (MG).